An investigation of how natural sciences teachers mediate learning of chemical reactions in Grade 9: a case study - Xipu, Bukelwa (Rhodes University, Faculty of Education, Department of Education, 2012)
This research study involves two Grade 9 Natural Sciences teachers from two schools in the Lady Frere District of the Eastern Cape. The reason for selecting these two teachers is that in 2009 they, like me, obtained an Advanced Certificate in Education (Science and Maths) from Rhodes University. As a result, we have a good working relationship. Furthermore, both teachers are actively involved in the Natural Sciences curriculum in the District and their schools are not far from the District Office where I work. The principal objective of this study was to investigate how Natural Sciences teachers mediated learning in order to enhance conceptual development and understanding of chemical reactions in Grade 9. It was triggered by the transformation in curriculum in South Africa as well as by my experience of working with Natural Sciences teachers in our rural district. The study is informed by an interpretive paradigm using a qualitative case study approach. The data was gathered by administering analysis of documents, semi-structured interviews, observations, field notes and journals. During the data analysis process, patterns and themes were illuminated using the inductive analysis method. Rich data sets in relation to the main research question on how Natural Sciences teachers mediated learning in order to enhance conceptual development and understanding of chemical reactions in Grade 9 emerged from the analysed data. The conclusions that can be drawn from the study indicate that when teaching chemical reactions, teachers should have adequate content knowledge as well as pedagogical content knowledge. It is thus recommended that teachers consider the prior knowledge of learners, use a variety of teaching and learning approaches including practical activities, to make learning meaningful. The major limitation of this study is that the two selected teachers do not represent the whole population of Grade 9 teachers in the Lady Frere District. Therefore, the findings cannot be generalized to represent the larger population. It is recognised, however, that within the qualitative inquiry, reliability and generalizability play a minor role.
Keywords: Science -- Study and teaching (Secondary); Science -- Study and teaching (Secondary) -- South Africa -- Eastern Cape; Chemical reactions; Science teachers -- South Africa -- Eastern Cape; Science teachers -- Rating of -- South Africa -- Eastern Cape